Kansas agritourism business owners’ perception of communication practices and intentions to expand business development - Raley, Lauren Elizabeth (Kansas State University, 2023)
Growing interest in local food and sustainable farming practices has led to an increase in agritourism operations. Agritourism is a sector of agriculture that connects the consumer and the agriculture industry. Research on Kansas agritourism is limited, and no studies investigate Kansas agritourism business owners’ perceptions of their communications and marketing efforts. Exploration of the importance and implementation of communication strategy by Kansas agritourism business owners can provide insight into the future growth, business motivation, and community impact these business owners possess. Identifying the barriers agritourism business owners face related to expansion and communication strategies provide insight into how to expand and improve the agritourism industry in Kansas. This study explored how Kansas agritourism business owners’ perceptions of communications practices relate to their intentions to expand their business through the lens of the Theory of Planned Behavior. The research questions of this study were addressed using a quantitative survey instrument distributed to registered Kansas agritourism business owners via email. The questionnaire inquired about the following areas: (1) current communication strategies and importance level of the respondent, (2) intentions to expand Kansas agritourism operations, (3) motivations and current business success, (4) respondent’s barriers related to business expansion and communication strategies and (5) profile of the responding agritourism business owner. The demographic characteristics of Kansas agritourism business owners were identified using descriptive statistics. Data analyses of variance and correlations were used to answer the research questions. This study revealed in-person, word-of-mouth promotion is the most important communication channel for agritourism business owners. The difference in perceived importance of digital communication channels was statistically significant between livestock operation, accommodation and vineyard/winery businesses. Print communication channels perceived importance was statistically significant and different between accommodation and vineyard/winery businesses. The difference in perceived importance of in-person communication channels was statistically significant between farms of all varieties, accommodation and vineyard/winery businesses. In addition, there was a positive relationship between Kansas agritourism business owners’ ability to promote their business and their perception of communication and marketing practices’ importance. Results from this study indicated Kansas agritourism business owners’ perception of communication practices and how they related to their intentions to expand their business. Adding a unique perspective to agritourism research, this study offers the perspective of agritourism business owners. The findings provide insight and recommendations for both state agritourism programs and agritourism business owners. It is recommended that future research continues to analyze agritourism from the business owners’ perspective by identifying the role and importance of communications within their business strategy. To encourage continued growth of the agritourism industry, is essential to understand what drives business owners to be successful and expand their businesses.
Keywords: Agritourism; Theory of Planned Behavior; Business owners